Effect of pharmacist-led intervention on predictors of diabetic neuropathy at two different hospitals of Malaysia - Amer Hayat Khan; Muhammad Zahid Iqbal; Syed Azhar Syed Sulaiman; Aznita Ibrahim; Nor Shaffinaz Binti Yusoff Azmi; Muhammad Shahid Iqbal (GarVal Editorial Ltda., 2021)
Context: Diabetes mellitus is a progressive disease. In poor glycemic control, it can cause severe and non-reversible complications. A proper educational intervention from health care providers is needed for patients to decrease the progression of diabetes and its complications. Aims: To evaluate the effect of pharmacist-led educational intervention on predictors of diabetic neuropathy in patients. Methods: From two tertiary care hospitals, diabetic patients were randomly selected and divided into the control and intervention groups. The control group contained 200 patients who were getting traditional treatment from hospitals. In contrast, the intervention group included 200 patients who were receiving conventional treatment together with separate counseling sessions with pharmacists. The study continued for one year, and four follow up visits for both groups. A pre-validated data collection form was used to collect data for the signs and symptoms of diabetic neuropathy. Statistical Package for the Social Sciences version 24 was used to analyze the data. Results: The average HbA1c values decreased by up to 1.96% in the control group and 3.41% in the intervention group from baseline data. A statistically significant (p<0.05) difference in HbA1c among both of the study groups at every follow-up. The results of univariate and multivariate regression analysis showed that a statistically significant difference was observed in the improvement of signs and symptoms of diabetic neuropathy among both of the study groups. Conclusions: Statistically significant reduction in the sign and symptoms of diabetic neuropathy was observed in the intervention group at the end of one year.